РОЛЬ ГЕОДИНАМІКИ В ТОРФОНАКОПИЧЕННІ ТА ФОРМУВАННІ РЕЧОВИННО-ПЕТРОГРАФІЧНОГО СКЛАДУ ВУГІЛЛЯ ЗАХІДНОГО ДОНБАСУ - Ivanova, А.; Zaitseva, L. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2014)
The geodynamic evolution mode of the Western Donbas affected the conditions of the peat accumulation, phytocenosis change, character of plant material transformation, formation of the coal petrographic composition and quality, defined geothermal condition of the region and the degree of organic matter metamorphism. According to Institute of geological sciences and other organization experts data there are the results of coal petrographic and geochemical studies of Petrykivskyi, Novomoskovskyi and Pavlogradsko-Petropavlivskyi areas. There is the conclusion about the relationship of recomposed coal types and its enrichment with sodium and chlorine with the conditions of peat accumulation and subsequent transformation of organic matter.